2020
DOI: 10.1038/s41598-020-69228-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytic transcriptional signatures predict comparative drug interaction potential of rifamycin antibiotics

Abstract: current strategies to treat tuberculosis (tB) and co-morbidities involve multidrug combination therapies. Rifamycin antibiotics are a key component of tB therapy and a common source of drugdrug interactions (DDis) due to induction of drug metabolizing enzymes (DMes). Management of rifamycin DDIs are complex, particularly in patients with co-morbidities, and differences in DDI potential between rifamycin antibiotics are not well established. DME profiles induced in response to tuberculosis antibiotics (rifampin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Ingenuity Pathway Analysis (IPA) software (Qiagen) was used to perform pathway enrichment, gene network, and upstream regulator analyses (URA) according to the standard protocols as previously described (39,40). A list of differentially expressed genes in a dataset with a minimum of 1.5-fold change and p value of <0.05 significance were compared between the two groups and uploaded into IPA.…”
Section: Rna Isolation and Gene Expression Analysismentioning
confidence: 99%
“…Ingenuity Pathway Analysis (IPA) software (Qiagen) was used to perform pathway enrichment, gene network, and upstream regulator analyses (URA) according to the standard protocols as previously described (39,40). A list of differentially expressed genes in a dataset with a minimum of 1.5-fold change and p value of <0.05 significance were compared between the two groups and uploaded into IPA.…”
Section: Rna Isolation and Gene Expression Analysismentioning
confidence: 99%
“…We considered the possibility that our observations could reflect differences in drug metabolism. Rifampicin induces gene expression changes in hepatocytes [ 29 , 30 ], but after reviewing this literature and publicly available RNASeq data (Gene Expression Omnibus, Series GEO139896) [ 29 ] we found no evidence for this (data not shown). This could also be attributed to the fact that our study focused on peripheral blood-associated gene expression changes as compared to the liver-derived hepatocytes described in these previously reported studies.…”
Section: Discussionmentioning
confidence: 96%
“…A similar trend was observed when mice with low n-3 PUFA status were supplemented with EPA/DHA, suggesting that the coadministration of EPA/DHA together with the currently used TB antibiotics has no observable adverse effects. Multidrug combination therapy approaches for TB treatment make it a candidate for possible drug-drug interactions (DDIs) or drugnutrient interactions (DNIs) (67), which subsequently may result in poor TB treatment outcomes and the emergence of drugresistant TB (68,69). Considering the recent interest and the prospects associated with the use of repurposed drugs and pharmaconutrients as an adjunct therapy in TB (35,(70)(71)(72), this study further reinforces the prospect for the use of n-3 LCPUFA # Data are reported as means ± SEM percentage of total fatty acids of n = 6 mice/group and representative of two independent experiments.…”
Section: Discussionmentioning
confidence: 99%